The noble families of Butovan and Botono in medieval Zadar : family structure, property reconstruction, and social life - Begonja, Sandra (Array, 2019)
This paper presents the genealogy (family structure), urban family estates, and social life of the Zadar-based noble families of Butovan and Botono during the 13th and 14th centuries (until the 1390s) in order to determine their similarities and differences (whether they were one or two different families).